Addition by Subtraction? A Longitudinal Analysis of the Impact of Deportation Efforts on Violent Crime. Issue 4 (21st October 2013) - Stowell, Jacob I.; Messner, Steven F.; Barton, Michael S.; Raffalovich, Lawrence E.
Abstract : Contemporary criminological research on immigration has focused largely on one aspect of the immigration process, namely, the impact of in‐migration (i.e., presence or arrival) of foreign‐born individuals on crime. A related but understudied aspect of the immigration process is the impact that the removal of certain segments of the foreign‐born population, and specifically undocumented or deportable aliens, has on aggregate levels of criminal violence. In an effort to cast new light on the association between forced out‐flows of immigrants and crime, we begin with descriptive analyses of patterns of deportation activity across the continental United States over an eleven‐year period (1994–2004). We then examine the relationship between deportation activity and violent crime rates in a multilevel framework wherein Metropolitan Statistical Areas (MSAs) are situated within border patrol sectors. The results of dynamic regression modeling indicate that changing levels of deportation activity are unrelated to changing levels of criminal violence for the sample of MSAs for the national at large. However, we also detect significant interactions by geographic location for selected violent offenses. For MSAs within sectors along the Mexican border, the deportation measure exhibits a significant negative effect on one indicator of criminal violence—the aggravated assault rate. For MSAs within non‐border sectors, the effect of the deportation measures is significantly positive for the violence crime index and the aggravated assault rate. Overall, our analyses indicate that the relationship between deportation and criminal violence is complex and dependent on local context.